Follow‐up after treatment of high‐grade cervical dysplasia: The utility of six‐month colposcopy and cytology and routine 12‐month colposcopy. (15th September 2020) - Morton, Rhett; Mylvaganam, Gaithri; Anderson, Lyndal; Farrell, Rhonda; Carter, Jonathan; Pather, Selvan; Saidi, Samir
Abstract : Background: Australian Cervical Screening Program guidelines no longer recommend colposcopy and cytology at six months following treatment of cervical intraepithelial neoplasia (CIN2/3) and a co‐test of cure can be performed at 12 months without colposcopy. Aims: To determine the usefulness of six‐month colposcopy and cytology and routine colposcopy with co‐testing at 12 months in detecting persistent or recurrent disease in patients treated for CIN2/3. Materials and Methods: We conducted a review of all patients with histologically proven CIN2/3 who underwent a cervical excisional procedure between March 2012 and March 2017 in one specialised centre. Results: We examined 1215 cases and 750 remained after exclusions for analysis. At six months (722 cases, 96.2%) seven of 42 (16.7%) patients with high‐grade cytology had a high‐grade colposcopy and 24 of 42 (57.1%) had a normal colposcopy. Persistent CIN2/3 was diagnosed in 12 cases (1.7%) and only 1/3 had a high‐grade colposcopy. Cytology was more useful than colposcopy in detecting persistent disease. At 12 months (638 cases, 85%) routine colposcopy at the time of co‐testing had a high false positive rate with all high‐grade changes negative on biopsy and co‐test. Recurrent CIN2/3 was diagnosed in five cases, and four had normal colposcopy at co‐testing. Conclusions: There may be a delay in detection of persistent/recurrent CIN2/3 in a small number of cases without six‐month colposcopy and cytology; however, it is not likely to negatively impact overall clinical outcome. Co‐testing at 12 months following treatment of CIN2/3 without colposcopy is safe and routine colposcopy at collection of the co‐test can be omitted.